Isolation and properties of lactate dehydrogenase isoenzyme from buffalo liver: Application in AST and ALT assay diagnostic kits - Mohamed S. Helmy, Hassan M.M. Masoud, Doaa A. Darwish, Mohamed M. Abdel-Monsef, Mahmoud A. Ibrahim (Journal of Applied Pharmaceutical Science, 2019)
Lactate dehydrogenase (LDH) enzyme is a major component of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) diagnosis kits. In this work, the LDH enzyme was purified and characterized from buffalo liver for direct application in the preparation of AST and ALT diagnosis kits. One major LDH (BLLDH) isoform and two other secondary LDH peaks were analyzed for buffalo liver by diethylaminoethyl (DEAE) cellulose chromatography. BLLDH was obtained by ammonium sulfate sedimentation and chromatographically separated on ion exchange and size-exclusion matrices. The isolated BLLDH has a specific activity of 17.6 units/mg proteins represented 16 folds and 32% recovery. BLLDH was manifested homogeneous on native and SDS gels with 35 kDa native mass. Optimum pH of BLLDH was displayed at pH 7.6. BLLDH activity was diminished by FeCl2 and SDS. The produced BLLDH is utilized in constructing of AST and ALT diagnosis kits that were sensible and analogous to trade ready kits.
Keywords: Lactate dehydrogenase, purification, characterization, buffalo liver, AST and ALT diagnostic kits.